Interplay of pathogens, cytokines and other stress signals in the regulation of dendritic cell function - Sabatte, Juan Atilio (2007)
Dendritic cells (DCs) are the only antigen-presenting cell capable of activating naïve T lymphocytes, and hence they play a crucial role in the induction of adaptive immunity. Immature DCs sample and process antigens, and efficiently sense a large variety of signals from the surrounding environment. Upon activation, they become capable to activate naïve T cells and to direct the differentiation and polarization of effector T lymphocytes. It is becoming increasingly clear that different signals are able to determine distinct programs of DC differentiation and different forms of immunity and tolerance. In the past few years many advances have been made in addressing the action exerted by pathogen-associated molecular patterns (PAMPs), cytokines, chemokines, and other less characterized stress molecules on the activity of DCs. In this review we focus on the multiplicity of innate signals able to modulate the functional profile of DCs. © 2007 Elsevier Ltd. All rights reserved.